English Translation of M. Bérard: Tumeur Embryonnaire Du Muscle Strié. [Embryonal Tumor of Striated Muscle]. Lyon Med 1894; 77: 52. (4th March 2019) - Raney, R. Beverly; Bergeron, Christophe; Parham, David
Abstract: We have chosen to translate what we believe to be the first publication of a well-documented case of a young patient with embryonal rhabdomyosarcoma. The author, M. Léon Bérard, was a hospital fellow working in the department of M. Vincent at the Charité Hospital. The document was presented to La Société des Sciences médicales de Lyon (The Society of Medical Sciences of Lyon, France), in July, 1894. The translation follows below.